Exposure to microplastics (<10 μm) associated to plastic bottles mineral water consumption: The first quantitative study. (15th June 2019) - Zuccarello, P.; Ferrante, M.; Cristaldi, A.; Copat, C.; Grasso, A.; Sangregorio, D.; Fiore, M.; Oliveri Conti, G.
Abstract: The uncontrolled introduction into the environment of plastic polymers have caused the dispersion of plastic fragments, known as Microplastics (MPs), that represent an important topic for public health. This study was the first to investigate the cause of the release of MPs in mineral waters and to estimate the concentration of MPs smaller than 10 μm both in number of particles and in mass unit. This study was carried out using a patent method regarding the extraction and analysis of MPs in more kind of matrix. Therefore, aims of this study were a) to assess the number of MPs with diameters of between 0.5 and 10 μm in mineral waters contained in plastic bottles, b) to evaluate if the physical-chemical properties of mineral waters and bottle quality could influence the release of MPs and, finally, c) to estimate the human daily exposure to MPs due to mineral water consumption. The Mps were found in every sample. The main concentration of MPs was 656.8 μg/L ± 632.9 or 5.42E+07 p/L ± 1.95E+07. The main diameter of detected MPs was 2.44 μm ± 0.66 (where p/L, where p was the number of MPs). The Estimated Daily Intake (EDI) for adults and children were 1, 531, 524 p/kg/body-weight/day corresponding to 40.1 μg/kg/body-weight/day and 3, 350, 208 p/kg/body-weight/day corresponding to 87.8 μg/kg/body-weight/day, respectively. The number of MPs contamination in bottled mineral waters was strongly correlated to the pH of waters and to plastic density of bottle. Otherwise, micrograms of MPs per liter and the MPs diameters were strongly affected by plastic thickness. The most mineral water brand contaminated by MPs was the one whose bottles were made from poor quality plastic. In absence of reference values, it was no possible carried out a risk assessment for MPs exposure. It is fundamental to establish the reference method of analysis to monitoring every source of human intake. Graphical abstract: Image 10849 Highlights: New patent method of extraction and analysis of Microplastics. Estimation of the concentration of Microplastics smaller than 10 μm both in number of particles and in mass unit. Influence of physical-chemical properties of mineral waters and bottle quality on release of Microplastics. Estimated Daily Intake of Microplastics for adults and children.